Station rotation blended learning sebagai alternatif metode pembelajaran Sejarah Kebudayaan Islam (SKI) - Mukharomah, Awwalina (Maliki Interdisciplinary Journal, 2024)
This paper aims to examine the station rotation blended learning method as an alternative in learning the history of Islamic culture. The increasingly rapid development of technology demands the education world to shift towards technology-based learning, especially for learning with complex substances such as the history of Islamic culture. Its material requires a comprehensive understanding by students, so a learning method is needed that can facilitate them to gain this understanding. The method used in this paper is library research, which was carried out by examining written sources about blended learning with the station rotation method concerning an alternative to the history of Islamic culture learning. The results show that blended learning with the station rotation type is a suitable learning method for the complexity of the history of Islamic culture learning both for students and teachers. The learning model that combines traditional learning with online learning in three different stations simultaneously through rotations carried out by students, can help them to appreciate and emphasize every aspect and moral value of the history studied according to the initial objectives of the history of Islamic culture learning subject.